2012
DOI: 10.5414/cnx77s104
|View full text |Cite
|
Sign up to set email alerts
|

Pain in end-stage renal disease: a frequent and neglected clinical problem

Abstract: Pain is a major health problem in end-stage renal disease (ESRD) affecting half of the dialysis patients; most of them experience a moderate to severe degree of pain. Nevertheless, the impact of chronic pain and its consequences are often underestimated. Sources of pain related to the uremic environment are renal bone disease (osteitis fibrosa cystica, amyloidosis, osteomalacia), osteoarthritis, calcific uremic arteriolopathy and peripheral neuropathy. Moreover, comorbid conditions such as ischemic peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 60 publications
2
72
0
6
Order By: Relevance
“…[1] Low back pain (LBP) is also one of the major causes of musculoskeletal pain in hemodialysis patients. [2] As LBP is a common health problem, many individuals experience LBP at some point their lives. [3] It mostly originates from bones, intervertebral discs, joints, muscles, ligaments, neural structures, and blood vessels.…”
mentioning
confidence: 99%
“…[1] Low back pain (LBP) is also one of the major causes of musculoskeletal pain in hemodialysis patients. [2] As LBP is a common health problem, many individuals experience LBP at some point their lives. [3] It mostly originates from bones, intervertebral discs, joints, muscles, ligaments, neural structures, and blood vessels.…”
mentioning
confidence: 99%
“…Past studies demonstrate that depression and pain are present in approximately 20% and 50%, respectively, of patients receiving chronic hemodialysis, and both are strongly associated with impaired health-related quality of life. This has led to efforts to elucidate their associations with other adverse outcomes, including mortality (1,2,(7)(8)(9)(10)(11)(12)(13)(14). As part of the Dialysis Outcomes and Practice Patterns Study, Lopes et al demonstrated that among patients on chronic hemodialysis, depression was independently associated with increased mortality and hospitalization (15).…”
Section: Introductionmentioning
confidence: 99%
“…(20) Chronic and acute pain are common among hemodialysis patients, (2,12,13) with emphasis to bone pain, (13) abdominal pain, (21) pain during the hemodialysis access puncture, (22) osteoarthritis, uremic arteriolopathy and peripheral neuropathy. (23) The intensity of pain and discomfort among patients are important, interfering with quality of sleep and daily living. (24) Nausea, rated as a relevant diagnosis by the nurses, has been documented in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%